Elementary School ELLs' Reading Skill Profiles Using Cognitive Diagnosis Modeling: Roles of Length of Residence and Home Language Environment. Issue 3 (23rd July 2013) - Jang, Eunice Eunhee; Dunlop, Maggie; Wagner, Maryam; Kim, Youn‐Hee; Gu, Zhimei
<x xml:space="preserve">Abstract</x> The study examined differences in reading achievement and mastery skill development among Grade‐6 students with different language background profiles, using cognitive diagnosis modeling applied to large‐scale provincial reading test performance data. Our analyses revealed that students residing in various home language environments show different reading achievement growth patterns. Earlier gaps in their reading achievement disappear the longer they reside in the target language community. Additionally, students who come from home environments where they use English and another language equally demonstrate higher skill mastery achievement levels, indicating that immigrant students' diverse home language environments do not adversely affect their reading achievement in the longer term. The study results support the evidence that multilingual home language environments are not a cause of low achievement; however, the achievement patterns of Canadian‐born English language learners (ELLs) do differ from their immigrant counterparts, revealing that time alone is not a sufficient condition of reading skill achievement. ELLs' outperformance of monolinguals after 5 years of residence is a result of ongoing instructional support and a rich linguistic environment. The study results hold important policy implications: The evaluation of ELLs' academic achievement and school effectiveness for accountability purposes should be based on longitudinal data that track their developmental growths.